2016
DOI: 10.1097/aci.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, air pollution, and allergic respiratory diseases: an update

Abstract: Over the last 50 years, global earth's temperature has markedly risen likely because of growing emission of anthropogenic greenhouse gas concentrations. Major changes involving the atmosphere and the climate, including global warming induced by human activity, have a major impact on the biosphere and human environment.Urbanization and high levels of vehicle emissions are correlated to an increase in the frequency of pollen-induced respiratory allergy prevalent in people who live in urban areas compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 48 publications
1
80
0
Order By: Relevance
“…In urban areas, common ragweed, for example, grows faster, flowers earlier and produces more pollen (Ziska et al 2003). A prolonged and intensified pollen season caused by climate change affects allergy sufferers and might increase the probability of developing new allergies (D'Amato et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In urban areas, common ragweed, for example, grows faster, flowers earlier and produces more pollen (Ziska et al 2003). A prolonged and intensified pollen season caused by climate change affects allergy sufferers and might increase the probability of developing new allergies (D'Amato et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increase in greenhouse gas emissions, especially anthropogenic carbon dioxide (CO 2 ), global warming has intensified over the past decades (D'Amato et al 2014). Cities might be seen as ''harbingers of climate change'' because urban CO 2 and temperature levels are already higher than in rural areas (Ziska et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, migrant children had higher rates of asthma compared to their parents, highlighting the critical role of early-life environmental factors in the pathogenesis of allergic disorders. Other studies have also demonstrated correlations between urbanization and high levels of vehicle emissions with increases in pollen-induced respiratory allergy in urban compared to rural populations [33]. …”
Section: First-generation International Immigrantsmentioning
confidence: 99%
“…Global warming has resulted in longer pollen seasons, changes in crop patterns, and pollen distribution patterns [33]. Environmental conditions specific to urban regions such as high nocturnal temperatures, increased atmospheric carbon dioxide, and nitrogen deposition provide favourable conditions for agriculture, leading to increased production of pollen and airborne allergenic protein loads [51-54].…”
Section: First-generation International Immigrantsmentioning
confidence: 99%